2017
DOI: 10.1080/10428194.2016.1277384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating early interim fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography with the SUVmax-liver-based interpretation for predicting the outcome in diffuse large B-cell lymphoma

Abstract: Interim F-FDG PET/CT is an effective predictor in patients with DLBCL, but the standard evaluating criteria were controversial. In this study, investigators tried to investigate whether the liver SUV (SUV)-based interpretation could improve the accuracy of predicting the outcomes, comparing with the Deauville five-point scale (5-PS) and the reduction rate of the maximum standardized uptake value (ΔSUV) criteria. In 119 patients, PET/CT after two chemotherapy cycles (PET2) were evaluated with the SUV-based inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 29 publications
3
34
1
Order By: Relevance
“…Recently, several studies have shown that PET/CT was a more valid prognosticator of survival for patients with DLBCL than traditional clinicopathologic factors such as IPI score [21][22][23][24][25]. Our results confirm that only iPET was a significant independent indicator of outcome for patients with DLBCL in the rituximab era.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, several studies have shown that PET/CT was a more valid prognosticator of survival for patients with DLBCL than traditional clinicopathologic factors such as IPI score [21][22][23][24][25]. Our results confirm that only iPET was a significant independent indicator of outcome for patients with DLBCL in the rituximab era.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, several studies have shown that PET/CT was a more valid prognosticator of survival for patients with DLBCL than traditional clinicopathologic factors such as IPI score [21][22][23][24][25]. Our results confirm that only iPET was a significant independent indicator of outcome for patients with DLBCL in the rituximab era.…”
Section: Discussionsupporting
confidence: 81%
“…Negative predictive values for 2-year progression-free status were generally above 80%, except in four studies [ 34 , 35 , 39 , 53 ]. In Mamot et al [ 39 ], the somewhat lower negative predictive value could possibly be explained because radiotherapy (administered regardless of PET results) was counted as an event and resulted in a lower EFS rate compared to other clinical trials.…”
Section: Discussionmentioning
confidence: 96%
“…We found widely ranging positivity rates between studies, which are mainly in agreement with the timing of interim PET between cycles and the criteria used. In an exploratory analysis on five studies [ 34 , 37 39 , 47 ] that performed interim PET strictly after 2 cycles of therapy and applied the Deauville scoring system we found a pooled estimated HR of 3.48 (95% CI 2.46–4.93) with a corresponding 95% prediction interval of 1.58–7.67 (Supplemental Fig. 3 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation